Language barriers for foreign / non-local medical and dental students in and around greater Noida the need for inclusion of local language classes in the curriculum - Sahil Thakar; Shivalingesh KK; Swati Sharma; Alankrita Chaudhary; Kuldeep Dhanker; Manish Sharma; Yash Deep Singh (Al Ameen Medical College, 2020)
Introduction: An opportunity for a student to pursue his favorite course from a foreign/ distant university is a dream come true. In the medical and dental profession where their patient interaction (preferably in the local language) is the basis of the learning process, students who might not understand the local language may face barriers in interaction and hamper their learning process. Aim: To assess the perspectives and attitudes of foreign/non-local students on the language barriers among medical and dental students and its effect on their learning process. Material and Methods: The study included 200 students (convenience sampling) in and around various colleges of Greater Noida who were foreigners and/or came from Non-Hindi speaking places. Their perspectives, attitudes and barriers faced were assessed through an online questionnaire which was pre-validated and pre-tested. The questionnaire consisted of 10 close-ended questions on a dichotomous scale. An additional question was also added wherein they were asked if they would prefer if they were taught Hindi as a part of their curriculum. Data was analyzed using SPSS version 22.0 and primarily, the chi-square test was applied for data analysis. Results: This study included a total of 106 (53%) foreign dental students and 94 (47%) students from Non-Hindi speaking places of India (Particularly North-Eastern India). It was revealed that a majority of the students (177, 88.5%) faced difficulties while interacting with the patients and needed help of their peers. The responses were found to be statistically significant (p<0.5). Most of them (178, 89%) could understand the local language but nearly half of them 101 (50.5%) revealed having difficulties in speaking the local language. Almost all (187, 93.5%) of the students also reported that it would be beneficial if they were taught the local language as a part of their curriculum. Conclusion: Students preferred that classes to learn the local language would be a part of their curriculum and such classes are suggested to familiarize the students to the local language. It would also be a benefit for them if they were also taught as to how to deal with certain cultural beliefs and practices of the local people so that it can be incorporated in their patient treatment methods.